Pengaruh Laba Kotor, Laba Operasi, dan Laba Bersih Dalam Memprediksi Arus Kas di Masa Pandemi COVID-19 pada Perusahaan Makanan dan Minuman di Bursa Efek Indonesia Tahun 2016-2020 - Imas Dian Oktarini; Abdul Hamid; Miya Dewi (PUTRA JAWA PUBLISHER, 2023)
The purpose of this study was to examine the effect of gross profit, operating profit, and net profit on cash flow during the COVID-19 pandemic in food and beverage companies on the Indonesia Stock Exchange in 2016-2020, a quantitative study using purposive sampling technique obtained a sample of 18 food and beverage company. By using the Multiple Regression Analysis method and using SPSS for Windows, a descriptive test was carried out and the results were normal distributed research data and passed the Multicollinearity Test, Heteroscedasticity Test and Autocorrelation Test. From the research, it can be concluded that: 1. Gross profit has a positive and significant effect on cash flow. 2. Operating profit has no significant effect on cash flow. 3. Net income has no significant effect on cash flow. 4. Gross profit, operating profit, and net profit simultaneously have a significant effect on cash flow.